The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, Hassan; Glawion, Dorit; Jankowsky, Felix; Mohamed, Mahmoud; Quirrenbach, Andreas; Rieger, Frank M.; Schwemmer, Stephanie; Wagner, Stefan (Arxiv, 2018)
(Abridged) Context. NGC 253 is one of only two starburst galaxies found to emit $γ$-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE) (E $>$ 100 GeV) and high-energy (HE) (E $>$ 60 MeV) spectra are crucial to study the underlying particle accelerators and cosmic-ray interaction and transport. Aims. The measurement of the VHE $γ$-ray emission of NGC 253 published in 2012 by H.E.S.S. was limited by large systematic uncertainties. Here, a measurement of the $γ$-ray spectrum of NGC 253 is investigated in both HE and VHE $γ$-rays. Methods. The data of H.E.S.S. observations are reanalysed using an updated calibration and analysis chain. The $Fermi$-LAT analysis employs more than 8 years of data processed using pass 8. The cosmic-ray particle population is evaluated from the combined HE--VHE $γ$-ray spectrum using NAIMA. Results. The VHE $γ$-ray energy spectrum is best fit by a power-law with a flux normalisation of $(1.34\,±\,0.14^{stat}\,±\,0.27^{sys}) × 10^{-13} \mathrm{cm^{-2} s^{-1} TeV^{-1}}$ at 1 TeV -- about 40 % above, but compatible with the value obtained in Abramowski et al. (2012). The spectral index $Γ = 2.39 ± 0.14^{stat} ± 0.25^{sys}$ is slightly softer than but consistent with the previous measurement. At energies above $\si
Gesehen am 18.06.2019